Gender differences in depression prevalence: the role of inflammation and somatic symptoms - Brett Silverstein; Deborah Perlick (Academia Mental Health & Well-Being)
The higher prevalence of depression among women compared to men, beginning at adolescence, has been widely reported. Several studies reviewed here suggest that much of this difference results because women exhibit a much higher prevalence than men beginning in adolescence of a disorder involving depression combined with many somatic symptoms. Also reviewed here are many studies that have found that high levels of inflammation lead to the development of depression plus these somatic symptoms. Finally, a few studies reviewed here suggest the hypothesis that inflammation may result from low social status experienced by women. More research is needed to test this hypothesis. The combination of these brief reviews suggests that a major role in explaining the higher prevalence of depression among females beginning at adolescence may be played by somatic depression resulting from inflammation possibly precipitated by low status.